2016
DOI: 10.1097/sla.0000000000001499
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Intraoperative Positive End-expiratory Pressure (PEEP) on Respiratory Outcome in Major Abdominal Surgery Versus Craniotomy

Abstract: Objectives In this study, we examined whether (1) positive end-expiratory pressure (PEEP) has a protective effect on the risk of major postoperative respiratory complications in a cohort of patients undergoing major abdominal surgeries and craniotomies, and (2) the effect of PEEP is differed by surgery type. Background Protective mechanical ventilation with lower tidal volumes and PEEP reduces compounded postoperative complications after abdominal surgery. However, data regarding the use of intraoperative PE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 39 publications
(46 reference statements)
2
43
0
1
Order By: Relevance
“…We used patient data from all sources to form one de-identified database, as previously reported by our group. [23][24][25] Patient involvement No patients were involved in setting the research question or the outcome measures, nor were they involved in developing plans for recruitment, design, or implementation of the study. No patients were asked advice on interpretation or writing up of results.…”
Section: Methods Study Populationmentioning
confidence: 99%
“…We used patient data from all sources to form one de-identified database, as previously reported by our group. [23][24][25] Patient involvement No patients were involved in setting the research question or the outcome measures, nor were they involved in developing plans for recruitment, design, or implementation of the study. No patients were asked advice on interpretation or writing up of results.…”
Section: Methods Study Populationmentioning
confidence: 99%
“…Two small RCTs have found that 10 cm H 2 O PEEP may confer additional physiologic benefit 6061. With regard to PPCs, a large retrospective study of more than 11 000 abdominal and intracranial operations showed an association between the use of at least 5 cm H 2 O PEEP and a significantly decreased odds of PPCs compared with less than 5 cm H 2 O PEEP (odds ratio 0.72, 0.61 to 0.85) 62. Of note, secondary analysis did not show a benefit for craniotomy patients, suggesting that PEEP’s protective effect may not extend to patients at lower risk for atelectasis.…”
Section: Evidence Based Strategies For Perioperative Lung Protective mentioning
confidence: 99%
“…Our study was conducted in the operating theatre setting and not in an intensive care unit where patients' lungs are more likely to be difficult to ventilate due to reduced compliance. Since controlling for compliance did not influence our outcomes, we believe that our findings are valid across the spectrum of compliance studied [3].…”
Section: Mechanical Ventilation Mode and Postoperative Pulmonary Compmentioning
confidence: 61%
“…Existing data suggest the presence of wide variability in peri-operative ventilation practices that are not driven by patient comorbidities or procedural characteristics [4]. We conclude, based on our own data, that in a majority of patients, volume-controlled ventilation with low driving pressure and optimal, procedure-specific PEEP [3,4]…”
Section: Mechanical Ventilation Mode and Postoperative Pulmonary Compmentioning
confidence: 61%
See 1 more Smart Citation